Troso e-module based on SSI to enhance students' reasoning thinking dimensions and environmental literacy - Al Manunal Akhnah; Agung Wijaya Subiantoro (University of Muhammadiyah Malang, 2025)
Low levels of students’ critical reasoning and environmental literacy can negatively influence their attitudes toward environmental issues in their surroundings. This study aimed to develop and evaluate the effectiveness of a Socio-Scientific Issue (SSI)-based electronic module on the topic of environmental change to enhance critical reasoning and environmental literacy among phase E senior high school (SMA/MA) students. The study employed a research and development design using the ADDIE model, comprising analysis, design, development, implementation, and evaluation phases. Feasibility testing by material and media experts yielded average scores of 3.36 and 3.55, respectively, indicating high validity. Practicality tests conducted by teachers and students produced scores of 3.78 and 3.57, while a readability test resulted in an average score of 3.59. These findings suggest that the e-module is highly feasible and user-friendly. Effectiveness testing revealed significant improvements in students' reasoning and environmental literacy following the module’s implementation. Thus, the SSI-based e-module is an effective instructional tool for promoting higher-order thinking and environmental awareness among students, particularly in addressing real-world issues through contextual and inquiry-based learning.